5G edge computing development and application for industrial internet - Chengyu ZHANG; Hongwu LI; Yang QU; Jinwu WEI (Dianxin kexue)
The modern communication network technology represented by 5G and the accompanying mobile edge computing technology play a crucial role in the connection of the industrial internet, closely integrating production factors and exerting the value of collaborative operations.By describing the basic development status and technical characteristics of 5G edge computing, the application method for the industrial internet field and the comparison with the traditional model were explained, a reference implementation solution for industry services was proposed, and the expected application scenarios were summarized.